The health system burden of chronic disease care: an estimation of provider costs of selected chronic diseases in Uganda - Stella, Nalukwago Settumba; Sedona, Sweeney; Janet, Seeley; Samuel, Biraro; Gerald, Mutungi; Paula, Munderi; Heiner, Grosskurth; Anna, Vassall (John Wiley & Sons, Ltd, 2015)
ObjectiveTo explore the chronic disease services in Uganda: their level of utilisation, the total service costs and unit costs per visit.MethodsFull financial and economic cost data were collected from 12 facilities in two districts, from the provider's perspective. A combination of ingredients-based and step-down allocation costing approaches was used. The diseases under study were diabetes, hypertension, chronic obstructive pulmonary disease (COPD), epilepsy and HIV infection. Data were collected through a review of facility records, direct observation and structured interviews with health workers.ResultsProvision of chronic care services was concentrated at higher-level facilities. Excluding drugs, the total costs for NCD care fell below 2% of total facility costs. Unit costs per visit varied widely, both across different levels of the health system, and between facilities of the same level. This variability was driven by differences in clinical and drug prescribing practices.ConclusionMost patients reported directly to higher-level facilities, bypassing nearby peripheral facilities. NCD services in Uganda are underfunded particularly at peripheral facilities. There is a need to estimate the budget impact of improving NCD care and to standardise treatment guidelines.
Keywords: non-communicable diseases, human immunodeficiency virus, cost, low- and middleincome countries, Uganda, health systems